Temáticas heideggerianas en El ser y la nada de Jean-Paul Sartre - Vinolo, Stéphane (2022)
In order to separate from an excessively idealistic reading of Husserl’s phenomenology, Sartre turned to Heidegger’s ontology. His main goal was then to establish a phenomenological ontology. However, the author argues that all the main concepts that Sartre found in Heidegger, that is, nothingness, anguish, death and finitude, are constantly redefined into the French philosopher’s philosophy. This gesture explains the rupture according to which when Heidegger’s philosophy is a philosophy of finitude and death, that of Sartre is a philosophy and life.